How Nanopores Influence Dry-Frame VP Pressure Sensitivity - Raj, Rohit; Jaiswal, Priyank; Wang, Yulun; Grammer, G. Michael; Weger, Ralf J. (Frontiers in Earth Science, 2021)
This paper investigates how nanopore size distribution influences dry-frame P-wave velocity (VP) pressure sensitivity. The study uses a set of twenty-three samples belonging to a single vertical core from the Mississippian-age Meramec formation of the mid-continent US. Individual samples had their facies interpreted, composition estimated, He-gas porosity (ΦHe) determined, and P-wave and S-wave transit times systematically measured for dry core-plugs in a 5–40 MPa loading and unloading cycle. Data from the unloading cycle were linearized in the log scale, and the slope of the best fitting line was considered as a representative of the dry-frame VP pressure sensitivity. A series of photomicrographs from each sample were analyzed using image processing methods to obtain the shape and size of the individual pores, which were mostly in the nanopore (10−6–10–9 m) scale. At the outset, the pore-shape distribution plots were used to identify and discard samples with excessive cracks and complex pores. When the remaining samples were compared, it was found that within the same facies and pore-shape distribution subgroups VP pressure sensitivity increased as the dominant pore-size became smaller. This was largely independent of ΦHe and composition. The paper postulates that at the nanopore scale in the Meramec formation, pores are mostly isolated, and an increase in the confining pressure increased the bulk moduli of the fluids in the isolated pores, which in turn increased the VP pressure sensitivity. The study proposes incorporating this effect quantitatively through a dual-fluid model where the part of the fluid in unconnected pores is considered compressible while the remaining is considered incompressible. Results start to explain the universal observation of why the presence of microporosity quintessentially enhances VP pressure sensitivity.